If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -39 = x Reorder the terms: -39 + 8x = x Solving -39 + 8x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -39 + 8x + -1x = x + -1x Combine like terms: 8x + -1x = 7x -39 + 7x = x + -1x Combine like terms: x + -1x = 0 -39 + 7x = 0 Add '39' to each side of the equation. -39 + 39 + 7x = 0 + 39 Combine like terms: -39 + 39 = 0 0 + 7x = 0 + 39 7x = 0 + 39 Combine like terms: 0 + 39 = 39 7x = 39 Divide each side by '7'. x = 5.571428571 Simplifying x = 5.571428571
| x^2-8+5=0 | | 5/2=x/1.5 | | x+(-5)=-4 | | -r+7(-r-3)=-85 | | (x5)/5=79 | | -3-6y=12 | | 8y-15=7y+2 | | -3(2-6n)=-114 | | 81/2h+40 | | 1,1/2 | | 2y-y=3 | | V^2+7v=-10 | | 3(6p+8)=168 | | -45*-23= | | 2w+2h=22 | | -4p=9p-26 | | 4-3x/2+5x | | 3x+3+x+7=180 | | 4-3x/2=5x | | -8+a=-16 | | 3x^2+13=121 | | 91=-7(-1-4m) | | 3y+5-8y+7= | | 8d-3d-2d+4-4d=0 | | -280/-14 | | 15/5 | | -2-c=-1 | | (x+18)/5-(3x-36)/6=9 | | 31=-18-2x | | 280/-14 | | 31=-18-2 | | 4=m+4 |